?-STATISTICAL BOUNDEDNESS - Et, M.; Choudhury, C.; Debnath, S. (Turkic World Mathematical Soc, 2025)
In this paper, we introduce and examine the concept of rho-statistical boundedness and give some relations between statistical boundedness and rho-statistical boundedness. We also introduce the notion of rho-statistical upper bound, rho-statistical lower bound, rho-statistical supremum and rho-statistical infimum and investigate their interrelationships.
Keywords: rho-statistical boundedness; rho-statistical convergence; rho-statistical supremum; rho-statistical infimum